To Compare the Efficacy of 1% Permethrain Lotion & Manual Reduction of Head Lice in Children - Uzma DM Rajar, Naviad Kazi, Sadia Kazi, Sumayya Kazi, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective: To compare the efficacy of 1% Permethrin lotion and manual reduction of head lice in children. Study Design: Prospective study. Place and Duration: Department of Dermatology, Isra University, Hyderabad, during January 2013 to June 2014. Material and Methods: Patients were selected from out patient department of Isra university hospital during January 2013 to June 2014, this is an open prospective study, 400 children aged (1 year to 12 years) had participated in study. Randomly divided the patients in two groups, each group contain 200 patients, two interventions were used in this study: manual reduction of head lice and single application of 1% permethrin lotion on the scalp for 12 hours. All patients visited 3 times, once at the time of enrollment, than on 7 day followed by the end of treatment on 14 day. Results: In both Groups A and B (total 400 children), 25% had no head lice, 60% had active pediculosis and 15% had inactive infestation. Proportion of children with pediculosis was similar in all age groups; female children were 3 times more likely to have active infection than males. Active infestation was detected in 21% of children, 63.8% showing evidence of current or past infestation with head lice. The prevalence of inactive infestation was 12.7%. On day 1, the difference was not statistically significant in both Group A and B. At day 7 there were significant differences in the numbers of nymphs ( =0.045) and adults ( =0.017) between the two groups. This pattern was also observed at day 14 (for nymphs =0.031 and for adults P=0.023). Conclusion: The results of this study suggest that manual reduction of head lice is an effective alternative to the use of 1% permethrin lotion in managing head lice infestation. Therefore, manual reduction of headlice can be considered a safe alternative treatment for patients with head lice.